PENYULUHAN PEMBUATAN MINYAK ATSIRI SEBAGAI PESTISIDA BAGI MADRASAH ALIYAH PERSIAPAN NEGERI KOYA BARAT - Siallagan, Johnson; Krimadi, Lodwyk N.; Abulais, Diana (LPPM Uncen, 2024)
West Koya is one of the areas that has the most fertile land among other villages/sub-districts in the Muara Tami District area. This area has a soil texture and is the most efficient planting medium for secondary crops, especially rice and vegetables. The pest that often appears annoying is the whitefly. The aim of carrying out this community service activity is to provide information about the dangers of continuous use of chemical pesticides and the manufacture of pesticides from essential oils which can be used to treat or prevent nuisance pests such as whiteflies. The stages of the service method used are the initial survey, implementation of activities including counseling and demonstrations, as well as evaluation activity. Apart from that, through this service, West Koya MA students gain their knowledge and students can socialize with the surrounding environment, especially families who have agricultural land. The material presented in this activity will be through counseling sessions and demonstrations. The results of the evaluation of the service activities were assessed as very good by the target group by giving a score with the criteria of very good with a frequency value of 17 and good with a frequency value of 7. The target group's satisfaction score is high because the service activities can help increase insight into the target group.